Способи залучення черкаськими інтернет-ЗМІ контенту користувачів соціальних мереж - Коваль, Світлана Валеріївна (Київський національний університет імені Тараса Шевченка, 2016)
У статті досліджено один з унікальних інструментів сучасного онлайн-середовища – контент, згенерований користувачами медіа. Констатовано, що такий контент є наслідком розвитку інтерактивності аудиторії в руслі технологій Web 2.0. Мета дослідження полягає в обґрунту- ванні природи явища «user-generated content» (UGC), що стає джерелом інформації для інтернет-ЗМІ. Поліфункціональність феномену UGC зумовила комплексний підхід до обрання методів дослідження, серед яких: методи аналізу, синтезу, систематизації та порівняння для вивчення різногалузевих студій; спостереження – для з’ясування способів уведення матеріалів користувацького контенту до журналістських; класифікації – для виокремлення різновидів такого контенту. Ретельне теоретико-практичне студіювання окресленого питання дало змогу зробити низку науково значимих висновків. Диференційовано різновиди контенту (відео-, фотоконтент, текстовий UGC, інфографіка та комбінований контент) соціальних мереж, який використовують журналісти для продукування власних матеріалів. Виокремлено способи застосування UGC регіональними інтернет-ЗМІ Черкащини: інформаційний привід, основний текст, доповнення, унаочнення, обрання кута подання в матеріалі, збагачення ексклюзивом. Наголошено, що користувацький контент не замінює професійний журналістський матеріал, але доповнює та розширює його.

In this study we explore the user-generated content as one of the most unique tools of modern online environment. The user-generated content results from the interactivity with audience that becomes possible through the Web 2.0 technologies. Being accessible and affordable to the general audience, these technologies are widely applied by the users to independently create and share their own content. The objective of the research is to explore and substantiate the nature of the user-generated content (hereinafter UGC) phenomenon as a source of information for the online media. Being a multifunctional phenomenon UGC requires a comprehensive approach to the selection of research methods. We use the methods of analysis, synthesis, systematization, and comparison to explore the content samples from the wide range of sources including the citizen journalism, media activism, complicity journalism, and marketing. A method of observation let us identify the ways of including the user-generated content to the journalists’ publications; we also use the method of classification to distinguish the different forms of UGC. Results and Conclusions. The user-generated content is increasingly becoming popular, especially among the users of social networks. Media pay much attention to the UGC, encouraging its expansion. Different forms of social networks’ content, such as video, digital images, text, infographics and combined content are widely used by journalists to produce their own media products. Cherkasy online publishers take user-generated content from the Facebook and VKontakte social networks’ personal pages for different purposes including the following: as a news-break, as a main text, as an addition to the product, as an illustration, as special focus determination, as an exclusive, etc. The user-generated content does not replaces the professional journalistic products, but rather complements and expands them. Special attention should be paid to the verification of the user-generated content.
How Cherkasy Online Media Utilize the Content Generated by Social Networks’ Users
Keywords: user-generated content; social networks; online media; internet; користувацький контент; соціальні мережі; мережеві ЗМІ